Revolutionizing Language Learning in the Gen-Ai Era Optimizing ChatGPT in a Merdeka Belajar Curriculum - Hakim, Arief Rachman (Journal of Blended and Technical Education, 2025)
Objective: This study aims to examine the potential integration of ChatGPT, as a language model based on generative artificial intelligence (GenAI), into the Merdeka Belajar Curriculum to support the increased effectiveness of student-centered language learning. Research Design & Methods: This study used a qualitative method with a desk study approach, analyzing 15 selected studies from a total of 157 initial entries relevant to the use of GenAI, specifically ChatGPT, in language teaching and learning. Findings: The review shows that ChatGPT can improve language skills such as reading, writing, speaking, and listening through personalized, adaptive, and real-time interactions. It was also shown to encourage active participation, learning autonomy, and intrinsic motivation. However, the implementation of ChatGPT demands serious attention to ethical issues, data privacy, and the readiness of educational institutions' infrastructure. In addition, there are research gaps, such as the lack of long-term studies, the dominance of English language learning contexts, and the lack of exploration in local language and cultural contexts. Implications & Recommendations: To optimize ChatGPT integration, educators need to design innovative pedagogical strategies that strengthen critical digital literacy and support the development of lifelong learning skills. Strong and inclusive educational policy support is also needed to ensure ethical and sustainable implementation. Contribution & Value Added: This study makes an important contribution to the discourse of GenAI integration in the Indonesian education sector, highlighting the potential for transforming language learning through technology and offering strategic directions for educators and policymakers.